2016
DOI: 10.1073/pnas.1601461113
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine Wnt/β-catenin signaling mediates proliferation of undifferentiated spermatogonia in the adult mouse testis

Abstract: Spermatogonial stem cells (SSCs) fuel the production of male germ cells but the mechanisms behind SSC self-renewal, proliferation, and differentiation are still poorly understood. Using the Wnt target gene Axin2 and genetic lineage-tracing experiments, we found that undifferentiated spermatogonia, comprising SSCs and transit amplifying progenitor cells, respond to Wnt/β-catenin signals. Genetic elimination of β-catenin indicates that Wnt/β-catenin signaling promotes the proliferation of these cells. Signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
93
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 53 publications
(67 reference statements)
13
93
1
1
Order By: Relevance
“…This study showed that stabilization of β-catenin, showing weaker impact on cell adhesion (Harada et al., 1999), reduced the GFRα1 + pool in vivo (Figure 2K). This was in agreement with enhanced differentiation, and largely consistent with the results of β-catenin deletion (Figures S3B–S3M; Takase and Nusse, 2016). Wnt/β-catenin signaling inhibits stem cell differentiation In many cases, e.g., interfollicular epidermis, small intestinal crypts, and embryonic stem cells (Kim et al., 2005, Lim et al., 2013, Sato et al., 2004).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study showed that stabilization of β-catenin, showing weaker impact on cell adhesion (Harada et al., 1999), reduced the GFRα1 + pool in vivo (Figure 2K). This was in agreement with enhanced differentiation, and largely consistent with the results of β-catenin deletion (Figures S3B–S3M; Takase and Nusse, 2016). Wnt/β-catenin signaling inhibits stem cell differentiation In many cases, e.g., interfollicular epidermis, small intestinal crypts, and embryonic stem cells (Kim et al., 2005, Lim et al., 2013, Sato et al., 2004).…”
Section: Discussionsupporting
confidence: 90%
“…This study reinforced and complemented the previous reports that combined in vitro culture with transplantation-based stem cell assays (Yeh et al., 2011, Yeh et al., 2012) and that analyzed the in vivo impact of β-catenin deletion (Takase and Nusse, 2016). First, because GFRα1 + and NGN3 + cells both form repopulating colonies in the recipient's testes after transplantation (Grisanti et al., 2009, Nakagawa et al., 2007), it was difficult to unambiguously link the results of the transplantation assay with the states of differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, exogenous Wnt6 did not enhance Axin2 mRNA levels or induce beta-catenin accumulation. These findings were surprising because (i) c-Myc is described as a well-known Wnt/beta-catenin-dependent target gene (100) and (ii) many reports describe that Wnt6-induced signaling is beta-catenin dependent (101, 102). Recent insights into the structural basis of ligand-receptor interaction (48), showing conservation of interacting binding structures, suggest that the induced signaling and function of a certain Wnt ligand might not be predicted by its structure per se .…”
Section: Wnt6 and Its Role During Diseasementioning
confidence: 99%
“…26 However, Rivas et al suggested that conditional deletion of β -catenin using Stra8 -Cre (express only in males beginning at postnatal day 3 27 ) has no effect on male fertility. 28 In a recent article, 29 Takase et al reported that WNT6 secreted by Sertoli cells activates WNT/ β -catenin signalling in undifferentiated spermatogonia, including SSCs, which mediate the proliferation but not the maintenance of undifferentiated spermatogonia.…”
mentioning
confidence: 99%
“…Collectively, previous studies have suggested that WNT signalling and WNTs play multiple roles in spermatogenesis, but there are still the following problems: (1) the conclusions about the function of WNT/ β -catenin in germ cells are inconsistent with each other; 26, 28, 29 (2) the overlapping expression pattern of the various WNTs and their functional redundancy obscure the true consequences of removing individual Wnt genes; and (3) β -catenin does play a central role in the canonical WNT pathway, but it also serves as a membrane protein of the cell junction complex. 30 …”
mentioning
confidence: 99%